Penguatan Manajemen Sumber Daya Manusia Kelompok Wanita Tani (KWT) Barokah melalui Pelatihan Dasar Organisasi - Abdullah Akhyar Nasution; Iromi Ilham; Ibrahim Chalid; Richa Meliza; Ade Ikhsan Kamil; Awaluddin Arifin (Jurnal Solusi Masyarakat (JSM), 2023)
The community service activity raised the title "Strengthening Human Resource Management of Barokah Women Farmer Group through Organizational Basic Training". The purpose of implementation is to increase the capacity of human resources in terms of management and governance of farmer groups to build a commitment to running the organization. During the pandemic, a group of women from Paloh Lada Village faced economic problems so they took the initiative to form a farmer group. They jointly explore their potential and then turn it into business opportunities, especially in the agricultural sector. However, along the way, this group was faced with various problems, one of which was organizational stagnation caused by the lack of human resource capacity in terms of organizational management and governance. For this reason, this service activity is carried out to provide a solution to this problem, namely by providing basic organizational training and motivating to continue to run the wheels of the organization together.